2019
DOI: 10.1186/s12909-019-1468-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of burnout in medical undergraduate students in Riyadh, Saudi Arabia

Abstract: BackgroundTo assess the prevalence of burnout symptoms among preclinical and clinical medical students studying at AlFaisal University in Riyadh, Saudi Arabia.MethodsA cross-sectional study was conducted using Maslach Burnout Inventory questionnaire on 276 medical students from Alfaisal University, Riyadh, Saudi Arabia. The study was approved by Alfaisal University research ethics committee. Chi-square test was used to identify statistically significant differences, and binary logistic regression was used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
4
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 46 publications
11
62
4
5
Order By: Relevance
“…[ 34 ] The burnout prevalence was 13.4% in medical students of Riyadh. [ 32 ] Burnout rates reported from Chinese and US medical schools were 50%, which is much higher than our population. [ 14 37 ]…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…[ 34 ] The burnout prevalence was 13.4% in medical students of Riyadh. [ 32 ] Burnout rates reported from Chinese and US medical schools were 50%, which is much higher than our population. [ 14 37 ]…”
Section: Discussionmentioning
confidence: 76%
“…Our burnout prevalence is similar to Brazilian, British, Pakistan, Romanian, and Saudi Arabian medical students. [ 31 32 33 34 35 ] Burnout rates reported in Brazilian medical students varied from 10.3% to 12%. [ 33 36 ] Of 18.2% of the medical students in Karachi reporting burnout, 20.7% of the students reported high burnout rates in EE, 19.8% low in PA, and 17.8% high in DP.…”
Section: Discussionmentioning
confidence: 99%
“…urban vs. rural). A study on medical students in Saudi Arabia also suggested that longitudinal studies should be conducted to explore the mental health patterns from admission to graduation (Altannir et al, 2019). Another conclusion drawn from the current research is the focus that needs to be given to mental health of medical students.…”
Section: Suggestionsmentioning
confidence: 75%
“…Some studies have shown that no difference exists between the sexes in predicting burnout (44,45). Some report that males are at a higher risk (46,47), while some indicate that female medical students are more vulnerable (48,49).…”
Section: Conceptual Frameworkmentioning
confidence: 99%